PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN, PERSEPSI RISIKO, TERHADAP KEPERCAYAAN DAN NIAT BELI E-TICKET PADA SITUS TRAVELOKA - Adi Putra, I Putu Agus Purnama; Sukaatmadja, I Putu Gde; Giantari, I G.A Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.09.TAHUN 2016, 2016)
The purpose of this study was to obtain empirical evidence Influence Perceived Ease of Use, Perceived Risk Of Trust and Intent to Buy E-Ticket On Site Traveloka. The sample was taken by purposive sampling technique. Indicators research counted 18 indicators and the total respondents were 180 people. Collecting data using questionnaire technique, which is where the questionnaire using a Likert scale with 5 possible answers 1 through 5 and analysis tools using SEM (Strucutral Equation Modeling). The result is that the perceived ease of use positive and significant impact on the trust and purchase intentions. Risk perception negatively affect purchase intentions and trust, and the trust has positive influence on purchase intentions. The theoretical implications of this research are not all variables are positive and significant effect as well as the influence of risk perception negatively affect purchase intentions. The practical implications are useful for companies to explore the perception of risk from a consumer standpoint. for the future, first consider the needs and desires on the purchase of e-ticket.
Keywords: Perceived Ease of Use, Perceived Risk, Trust and Intent to Buy